A determination of the prevalence of palliative care patients admitted to the Groote Schuur Hospital Emergency Centre and their Presenting Complaints - Govender, Radha (Department of Medicine, 2023)
Background: The Emergency Centre is often an entry point to health services and is, therefore, well positioned to identify patients with palliative care needs. It is also the place of care sought by the families of palliative care patients when their loved ones are seriously ill or terminal. It becomes important to understand the numbers of palliative care patients presenting to Emergency Centres and the reasons why they present there, in order to strengthen the care provided to these patients in the Emergency Centre. Objectives: This study aimed to determine the prevalence of palliative care patients in a tertiary academic hospital Medical Emergency Centre, and to establish their presenting complaints. Method: The study was an exploratory and descriptive quantitative study based on a review of folders of admitted patients. Non-random sampling with a convenience sampling method was used. Data collection was carried out from 01-11 August 2019. Folders of patients admitted to the Emergency Centre were reviewed, data was collected onto an excel workbook, and analysed. Data collected included patient demographics, symptoms, diagnoses, reasons for presentation, and previous history of palliative care services. Results: Over the data collection period, 383 patients were admitted to the Emergency Centre. 124 of these patients were found to have palliative care needs. Palliative care prevalence over the measured period in the Emergency Centre was therefore 32.4%. Forty-eight percent (48%) of the palliative care patients were male, 52% were female. The most frequent reasons for admission to the Emergency Centre were pain (14% of patients), shortness of breath (7%), loss of/reduced levels of consciousness (6%), and heart disease (5%). 35% of patients presented during business hours (8am-4pm), 62% presented after hours (4pm- 8am). The most frequent reason for admission after hours was pain (18% of palliative care patients admitted after hours). There were no pain- related reasons for admission during business hours. Shortness of breath and heart disease were the most frequent reasons for admission during business hours – forming 6.8% each of all palliative care related business hour admissions. The most frequent symptoms noted for palliative care patients were pain (32.0%), loss of/reduced level of consciousness (30.6%), shortness of breath (24.2%). The most common palliative care related diagnoses were heart/vascular disease (29,0%), cancer progressive and/or metastatic (26.6%) and neurological disease/stroke (19.4%). The top 3 diagnoses in both females and males were hypertension, heart disease and cancer. The most frequent symptom presented by cancer patients was pain. Hospice services are available in the vast majority (96%) of the suburbs in which the patients reside. Only 5.6% of the palliative care patients had been referred to palliative care services. Conclusion: The Emergency Centre is an important catchment zone for the identification and management of palliative patients. Understanding the expected volume of palliative care patients in an Emergency Centre will allow staff to plan for their special needs. The prevalence of palliative care patients presenting to an Emergency Centre is 32.4%. To better support palliative care patients, it is important to understand why patients with palliative care needs present to an Emergency Centre. Pain, shortness of breath and loss of/reduced levels of consciousness are driving patients to the Emergency Centre. While South Africa has a preliminary level of integration of palliative care services with health services, palliative care services are not available to patients and their families on weekends and after hours. Until this has been remedied and other sources of care are in place, Emergency Centres remain an important site of access to care for distressed patients. This therefore requires that a palliative care approach be followed to meet patient needs, and that palliative care training is prioritised for healthcare professionals working in an Emergency Centre.